Acute:chronic workload ratio of professional soccer players preceding hamstring muscle injuries: a 2-season retrospective study - Ribeiro-Alvares, J. B.; Cetolin, T.; Haupenthal, A.; Baroni, B. M. (Sport Sciences for Health, 2024)
Purpose Given the controversial use of the Acute:Chronic Workload Ratio (ACWR) in determining the availability of soccer players for training and matches, this study aimed at verifying how many professional soccer players had an ACWR above 1.5 (considered a `danger zone`) immediately before the exposure (training or match) in which they sustained a hamstring muscle injury.